Cultivating Critical Thinking of EFL Secondary School Through Podcasts in MA Terpadu Al Hidayah Sumenep - Yusroni Farlan; Estu Widodo; Santi Prastiyowati (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This study is grounded in the growing urgency to utilize podcasts as a promising digital medium in English as a Foreign Language (EFL) instruction in Indonesia, particularly for fostering students’ critical thinking skills. The study aims to explore the experiences of students at MA Terpadu Al Hidayah Sumenep in using podcasts and to identify the supporting and inhibiting factors in the development of critical thinking through this activity. Employing a qualitative approach with a case study design, data were collected through in-depth interviews, focus group discussions, participant observation, and document analysis. Thematic analysis revealed that podcasts contributed to three major dimensions of critical thinking: more structured argument construction, more selective evaluation of evidence and information, and deeper metacognitive reflection. Although the extent of development varied among students, podcasts proved to be an effective medium for encouraging participation, collaboration, and critical awareness in EFL learning. These findings affirm that the integration of digital media can bridge religious-based educational traditions with the demands of 21st-century skills, while also offering practical implications for English teachers in designing more participatory and reflective learning experiences.